Strategi Pemasaran Digital untuk UMKM Desa: Meningkatkan Keberlanjutan Usaha Mikro melalui Platform Media Sosial di Desa Sikeben - Asrifah Nabila; Muhammad Haikal Amril Tanjung; Wahyu Pinastia Ningrum; Zahra Safira; M. Fakhriza (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This research aims to identify and design relevant digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) in Sikeben Village, with the goal of enhancing business sustainability through the utilization of the village’s social media platforms. The study employs a descriptive qualitative approach using interviews, observations, and documentation analysis involving MSME entrepreneurs, village officials, and social media managers of the village. The findings indicate that leveraging the village’s social media can expand market reach, improve customer interaction, and construct a positive image of local products. However, challenges remain, such as limited digital literacy, internet infrastructure issues, and a lack of systematic content strategies. As a result, the study proposes a community-based digital marketing model, which includes market segmentation, strengthening local content, stakeholder collaboration, and data-driven evaluation.